2022
DOI: 10.1186/s12877-022-03334-7
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a randomized controlled trial of mindfulness-based stress reduction to improve attentional control in older adults (HealthyAgers trial)

Abstract: Background Mindfulness meditation is a form of mind–body intervention that has increasing scientific support for its ability to reduce age-related declines in cognitive functioning, improve affective health, and strengthen the neural circuitry supporting improved cognitive and affective health. However, the majority of existent studies have been pilot investigations with small sample sizes, limited follow-up data, and a lack of attention to expectancy effects. Here, we present the study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…Moreover, our findings indicate a significant enhancement in attentional control following the intervention, which was also significantly correlated with the MIED programme registration days. Consistent with several randomized control studies, the efficacy of 8-week mindfulness training interventions has been demonstrated in improving attentional control, manifested in improvements in momentary attentional control during daily life (Chin et al 2021), behavioural measures of attentional control (Prakash et al 2022) and electrophysiological markers of attentional control (Klee et al 2020;Moore et al 2012). Consequently, the MIED programme exhibits a pronounced impact on mitigating emotional distress (anxiety and depression levels) and enhancing attentional control, akin to other widely utilized MBIs.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Moreover, our findings indicate a significant enhancement in attentional control following the intervention, which was also significantly correlated with the MIED programme registration days. Consistent with several randomized control studies, the efficacy of 8-week mindfulness training interventions has been demonstrated in improving attentional control, manifested in improvements in momentary attentional control during daily life (Chin et al 2021), behavioural measures of attentional control (Prakash et al 2022) and electrophysiological markers of attentional control (Klee et al 2020;Moore et al 2012). Consequently, the MIED programme exhibits a pronounced impact on mitigating emotional distress (anxiety and depression levels) and enhancing attentional control, akin to other widely utilized MBIs.…”
Section: Discussionmentioning
confidence: 53%
“…2021), behavioural measures of attentional control (Prakash et al. 2022) and electrophysiological markers of attentional control (Klee et al. 2020; Moore et al.…”
Section: Discussionmentioning
confidence: 99%
“…The data used for the current study were collected as part of a randomized controlled trial designed to examine the effects of two mind-body interventions on attentional control in healthy older adults ( Prakash et al. , 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were initially recruited from the greater Columbus, Ohio area through a combination of advertisements and community outreach events. Detailed inclusionary and exclusionary criteria for the parent study have been published in the study protocol paper ( Prakash et al. , 2022 ).…”
Section: Methodsmentioning
confidence: 99%